Enhancement of Fluorescent Labeling via a Composited Thin Film - Taikei Suyama; Xiaowei Ji; Yaoju Zhang (International Journal of Polymer Science)
Fluorescent labeling is the prevailing imaging technique in cell biological research. When statistical investigations on a large number of cells are involved, experimental study is required for both low magnification to get a reliable statistical population and high contrast to achieve accurate diagnosis on the nature of the cells’ perturbation. As microscope objectives of low magnification generally yield low collection efficiency, such studies are limited by the fluorescence signal weakness. To overcome this technological insufficiency, Le Moal et al. proposed a method based on metal-coated substrates that enhanced the fluorescence process and improved collection efficiency in fluorescence microscope observation and that could be directly used with a common microscope setup. In this paper, we use an Ag-Si3N4-Ag multilayer film coated on the substrate and numerically analyse the optical behavior of a fluorophore which was placed above the composited film coated on the substrate. The results shows that by using an Ag-Si3N4-Ag composited film the fluorescence imaging can be enhanced remarkably.